If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(k + -6) = 4k + 2 Reorder the terms: 2(-6 + k) = 4k + 2 (-6 * 2 + k * 2) = 4k + 2 (-12 + 2k) = 4k + 2 Reorder the terms: -12 + 2k = 2 + 4k Solving -12 + 2k = 2 + 4k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-4k' to each side of the equation. -12 + 2k + -4k = 2 + 4k + -4k Combine like terms: 2k + -4k = -2k -12 + -2k = 2 + 4k + -4k Combine like terms: 4k + -4k = 0 -12 + -2k = 2 + 0 -12 + -2k = 2 Add '12' to each side of the equation. -12 + 12 + -2k = 2 + 12 Combine like terms: -12 + 12 = 0 0 + -2k = 2 + 12 -2k = 2 + 12 Combine like terms: 2 + 12 = 14 -2k = 14 Divide each side by '-2'. k = -7 Simplifying k = -7
| 4.3V-6=8T | | -5p+1=75 | | -10p=30 | | (7x+8)(3x-4)=0 | | 3[2x+5]=9x-6 | | 2x+18=-6x+13 | | -2(3w+4)=3w-5 | | 4(5x+2)+4x+2x+5=403 | | 8(x-9)(2x+9)=0 | | -3(5x-7)= | | 56+80=12+8 | | 20-7y=10 | | 6r=-18 | | 6x-(2x+3)=9 | | 28-.3y=.7-12 | | 91=(99+86+76+95+x)/5 | | (3x-5)(3x-5)=25 | | x^2+3*x-5=175 | | 2x=-34 | | 2+(x+1)+5x=4 | | 7(A-6)= | | 7(X+4)=4X+3 | | 3(x+12)=30 | | 4n+6-2n=2(n+6) | | 7y+3=2x | | -3(x+8)=13x+1 | | 7N-2N+3P+2P= | | -15x=240 | | 2x=7y+3 | | 2-3p=0 | | b/5-3/4=1/2 | | 3(4xy+2x^2+5x^3y)= |